Sulodexide versus Control and the Risk of Thrombotic and Hemorrhagic Events: Meta-Analysis of Randomized Trials - Bikdeli, Behnood; Chatterjee, Saurav; Kirtane, Ajay J.; Parikh, Sahil A.; Andreozzi, Giuseppe M.; Desai, Nihar R.; Francese, Dominic P.; Gibson, C Michael; Piazza, Gregory; Goldhaber, Samuel Z.; Eikelboom, John W.; Krumholz, Harlan M.; Stone, Gregg W. (Seminars in Thrombosis and Hemostasis, 2020)
Thrombotic cardiovascular disease (myocardial infarction [MI], stroke, and venous thromboembolism [VTE]) remains a major cause of death and disability. Sulodexide is an oral glycosaminoglycan containing heparan sulfate and dermatan sulfate. We conducted a systematic review and meta-analysis to determine the cardiovascular efficacy, and safety of sulodexide versus control in randomized controlled trials (RCTs). We searched MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials for RCTs reporting cardiovascular outcomes in patients receiving sulodexide versus control (placebo or no treatment). Outcomes included all-cause mortality, cardiovascular mortality, MI, stroke, deep vein thrombosis (DVT), pulmonary embolism, and bleeding. We used inverse variance random-effects models with odds ratio (OR) as the effect measure. After screening 360 records, 6 RCTs including 7,596 patients (median follow-up duration: 11.6 months) were included. Patients were enrolled for history of MI, VTE, peripheral arterial disease, or cardiovascular risk factors plus nephropathy. Use of sulodexide compared with control was associated with reduced odds of all-cause mortality (OR 0.67, 95% confidence interval [CI] 0.52–0.85, p = 0.001), cardiovascular mortality (OR 0.44, 95% CI 0.22–0.89, p = 0.02), and MI (OR 0.70, 95% CI 0.51–0.96, p = 0.03), and nonsignificantly reduced odds of stroke (OR 0.78, 95% CI 0.45–1.35, p = 0.38). Sulodexide was associated with significantly reduced odds of VTE (OR 0.44, 95% CI 0.24–0.81, p = 0.008), including DVT (OR 0.41, 95% CI 0.26–0.65, p < 0.001), but not pulmonary embolism (OR 0.92, 95% CI 0.40–2.15, p = 0.86). Bleeding events were not significantly different in the two groups (OR 1.14, 95% CI 0.47–2.74, p = 0.48). In six RCTs across a variety of clinical indications, use of sulodexide compared with placebo or no treatment was associated with reduced odds of all-cause mortality, cardiovascular mortality, MI, and DVT, without a significant increase in bleeding. Additional studies with this agent are warranted.
Keywords: sulodexide; cardiovascular; venous thromboembolism; myocardial infarction; bleeding